SWINBURNE'S SEA-PROSE AND THE ANTI-NOVEL. Issue 2 (5th May 2017) - Yamboliev, Irena
Abstract : Language can be made to revolt against its own instrumentality. That is the promise Algernon Charles Swinburne pursues in his unfinished novel Lesbia Brandon, composed in 1859–67 but not published until 1952. Early on in this work, we encounter a passage that perfectly showcases his peculiar and innovative prose style. It is a style that boldly invents its own mechanism of self-perpetuation, and, as it ramifies throughout the novel, turns the text into something other than a conventional narrative – a singular grammar of sensuous perception. The novel's young protagonist, Herbert Seyton, has rounded a corner of a coastal road and comes face to face with the sea. Lesbia Brandon is full of descriptions of the natural environment like this one. It is one of many moments in the novel in which characters encounter, experience, and merge with the seascape. These instances concatenate Swinburne's formal project throughout Lesbia Brandon, a project of translating forces that create patterns in the perceived world into models for prose. The resulting stylistic transformation extends not only to the figurative aspects of Swinburne's language but also to its grammatical and syntactic underpinnings, as peripheral, "accessory" elements become core shaping forces in the prose. This process is at work as Herbert rejoices in the sea-coast and all its enchantments:The long reefs that rang with returning waves and flashed with ebbing ripples; the smooth slopes of coloured rock full of small brilliant lakes that fed and saved from sunburning their anchored fleets of flowers, yellower lilies and redder roses of the sea; the sharp and fine sea-mosses, fruitful of grey blossom, fervent with blue and golden bloom, with soft spear-heads and blades brighter than fire; the lovely heavy motion of the stronger rock-rooted weeds, with all their weight afloat in languid water, splendid and supine; the broad bands of metallic light girdling the greyer flats and swaying levels of sea without a wave; all the enormous graces and immeasurable beauties that go with its sacred strength; the sharp delicate air about it, like breath from the nostrils and lips of its especial and gracious god; the hard sand inlaid with dry and luminous brine; the shuddering shades of sudden colour woven by the light with the water for some remote golden mile or two reaching from dusk to dusk under the sun; shot through with faint and fierce lustres that shiver and shift; and over all a fresher and sweeter heaven than is seen inland by any weather; drew his heart back day after day and satisfied it. (196-97; ch. 2) This description consists of just one sentence, containing 209 words and eleven semicolon-separated fragments. With its great length and accumulation of clauses alone, this passage announces that Swinburne's narrative practice will warp the dimensions of prose, stretching its habitual units, the sentence and the paragraph, beyond their usual span. This sentence is remarkable for its almost complete absence of verbs. Almost every one of its verbs ("rang, " "flashed, " "fed, " "saved, " "go, " "shiver, " "shift") appears in a subordinate, defining clause that elaborates on the seascape's features. These verbs, for example, add specificity to the "long reefs" "that rang with returning waves and flashed with ebbing ripples, " point to the small lakes "that fed and saved from sunburning, " define the immeasurable beauties "that go with [the sea's] sacred strength, " and name the lusters "that shiver and shift." At the sentence's conclusion, two predicates finally reveal its raison d'être in terms of plot: the wonders of the sea " drew his heart back day after day and satisfied it." These are the events that motivate the description of the sea, but for most of the sentence's unfolding they are eclipsed, bowled over by the shimmering grammatical elaboration. Swinburne insistently adds adjectives to his nouns, singly and in multiples: "long reefs, " "returning waves, " "sharp slopes, " "small brilliant lakes, " "blue and golden bloom, " "sharp delicate air, " "dry and luminous brine, " "faint and fierce lustres." Sometimes the adjectives are comparatives ("yellower lilies and redder roses"), and at others Swinburne piles adjectives all around a noun, surrounding it in a halo of modifiers, as in "the sharp and fine sea-mosses, fruitful, " "the hard sand inlaid, " and "sudden colour woven." The adjectival imperative is so strong that it infiltrates and dilutes the verbs' efficacy to signal action. In addition to the defining verbs ("that rang, " "that fed, " "that go, " "that shiver and shift"), two more verbs appear near the end of the passage in the form of the participles "girdling" and "reaching." These do not name events but rather describe an enduring arrangement of "broad bands of metallic light" and a recurrent effect of water and light "reaching from dusk to dusk." They, too, contribute to the adjectival mode that dominates this prose.